High Performance Liquid Chromatography : Theory, Instrumentation and Application in Drug Quality Control - Al Sayed Omar, Omar (De Gruyter, 2022)
During the past decade, modern high-performance liquid chromatography (HPLC) utilization has expanded greatly, especially in the quality control of pharmaceutical products in drug quality control laboratories. This book provides an extensive collection of technical information about HPLC-Columns (physicochemical properties and chromatographic characteristics), from various manufacturers, and helps analysts to decide on the ideal approach for their analysis according to the requirements of drug manufacturers specifi cations and the desired Pharmacopeia. In addition, the authors give practical advice on how to prepare mobile phases, choose a suitable detector, and set up an HPLC analysis. This book is comprehensive for the average professional or technician who plans to work with modern HPLC. This book is useful for most Drug Quality Control Laboratories where modern HPLC is utilized. Following a hands-on approach, the book gives key insights into the pharmaceutical applications of HPLC and the latest requirements of the major regulatory agencies such as ICH, FDA, or USP.